1997
DOI: 10.3109/09273949709085061
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic analysis of retinal leukocyte infiltration during combined cyclosporin a and nasal antigen administration of retinal antigens: delay and inhibition of macrophage and granulocyte infiltration

Abstract: Nasal antigen administration successfully suppresses a model of organ-specific autoimmune disease, experimental autoimmune uveoretinitis (EAU)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…However, subsequent extensive investigations of the microglial cell have concluded that its main role is an immunosuppressive one, at least in the non‐inflamed retina (77–79). Instead, a second very small population of perivascular MHC class II + DCs and macrophages that line the retinal vessels in meningeal extensions were thought to be cells with the potential to initiate retinal inflammation (80) (). These cells are analogous to the perivascular CD11c + cells in the brain parenchyma, which, in elegant conditional knockout studies, have been shown to be required for induction of experimental autoimmune encephalitis (EAE) in mice (81).…”
Section: Myeloid Cells In Ocular Tissuesmentioning
confidence: 99%
“…However, subsequent extensive investigations of the microglial cell have concluded that its main role is an immunosuppressive one, at least in the non‐inflamed retina (77–79). Instead, a second very small population of perivascular MHC class II + DCs and macrophages that line the retinal vessels in meningeal extensions were thought to be cells with the potential to initiate retinal inflammation (80) (). These cells are analogous to the perivascular CD11c + cells in the brain parenchyma, which, in elegant conditional knockout studies, have been shown to be required for induction of experimental autoimmune encephalitis (EAE) in mice (81).…”
Section: Myeloid Cells In Ocular Tissuesmentioning
confidence: 99%
“…EAU is induced in mice by immunization with retinal antigens, and is a model for human posterior uveitis, a potentially blinding inflammatory ocular condition that affects the choroid of the eye and the neural retina (15, 16). Many studies have identified macrophages as key players in EAU, mainly in the context of the induction and effector phase of the disease (17, 18), although several reports have indicated the presence of macrophages in the resolution stage, as well (19, 20). However, in most of these studies there was no functional distinction between resident microglia and infiltrating macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…The release of inflammatory mediators leads to a leucocyte influx that consists of a complex mixture of cell types. 3,4 For example, at the peak of experimental autoimmune uveoretinitis (EAU), the murine model of human inflammatory eye disease, we observe a heterogeneous population of cells including CD11b + cells, which form the largest fraction of the immune cells present, with significant numbers of CD4 + T cells and smaller numbers of CD8 + T cells also detected. [5][6][7] In this environment, the large majority of CD11b + cells are usually described as macrophages (Mu); they release inflammatory mediators and act as professional antigen-presenting cells (APCs).…”
Section: Introductionmentioning
confidence: 99%